Factors Related To The Occurrence Of Pulmonary Tuberculosis In The Working Area Of Padang Serai Helath Center, Bengkulu City - Efendi, Heru; Surahman, Fery; Suyanto, Jipri; Darmawansyah, Darmawansyah; Wulandari, Wulandari (LPPJPHKI Universitas Dehasen Bengkulu, 2023)
Intoduction: Pulmonary tuberculosis is an infectious disease caused by the bacterium Mycobacterium tuberculosis that attacks the lungs and bronchi. Unhealthy lifestyles can lead individuals to be infected with tuberculosis, influenced by factors such as age, gender, education, knowledge, attitudes of patients, occupation, nutritional status, the role of health workers, housing density, and the environment. The aim of this study is to identify the factors associated with the incidence of pulmonary TB in the working area of Padang Serai Health Center in Bengkulu City. Method: The method used is a case-control study design, with data collected as primary data by distributing questionnaires to 30 cases with BTA (+) and 30 controls with BTA (-) in the working area of the Health Center in 2023 using total sampling technique. Result and Discussion: Data analysis was performed using the Chi-Square test. The results of univariate analysis showed that almost half of the respondents (45.0%) had low knowledge, more than half of the respondents (56.7%) lived in crowded conditions, and more than half of the respondents (55.0%) had an economic status of ≥Rp. 2,701,256. Bivariate analysis revealed there is a relationship between knowledge and the incidence of pulmonary TB (p=0.008), a relationship between housing density and the incidence of pulmonary TB (p=0.004), and a relationship between economic status and the incidence of pulmonary TB (p=0.038). Conclusion: The researchers recommend that the Health Center improve the role of health workers in educating patients about pulmonary tuberculosis.